Evaluasi Kebijakan Manajemen Bencana di Indonesia: Studi Kasus dan Implikasi untuk Penanganan Bencana Berkelanjutan - Nurfitriani, Widya; Saepudin, Eli Apud; Istyaningrum, Nabila Astuti; Apriliyaningsih, Siti; Sari, Della Puspita; Muslimah, Ima (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to evaluate disaster management policies in Indonesia with a focus on a case study of sustainable disaster management. Given Indonesia's vulnerability to various natural and non-natural disasters, it is important to formulate policies that are effective and adaptive. The method used in this research is descriptive qualitative approach, with literature analysis and case studies as the main strategies. as the main strategies. The results show that policy reformulation policies are needed in each phase of disaster management, namely pre-disaster, emergency response, and post-disaster. Some policy recommendations include increasing adequate funding, applying the principle of “build back better” in post-disaster recovery, and strengthening cooperation in post-disaster recovery. better” principle in post-disaster recovery, and strengthening cooperation between the government and the private sector. government and the private sector. This research provides important implications for development of a more sustainable disaster management strategy in Indonesia, and emphasizes the need for all parties to be involved in the disaster management process to achieve better resilience to disasters. process to achieve better resilience to disaster risk in the future. the future.